Immunological Impact of Whey Protein on Peripheral Blood Mononuclear Cells of Patients with Chronic Liver Disease - Mizubuti, Yani G.G.; Correia, Maria I.T.D.; da Silva, Thales A.; de Vasconcelos Generoso, Simone; Teixeira, Antônio L.; Lima, Agnaldo S.; Vieira, Érica L.M. (Current Nutrition & Food Science, 2021)
Background: Recent in vitro studies point to the immune properties of milk proteins. Objective: To investigate the immunomodulating properties of whey protein isolate (WHEY) compared to those of casein (CAS) on peripheral blood mononuclear cell (PBMC) death and supernatant cytokine levels in chronic liver disease (CLD) patients and healthy individuals. Methods: The role of WHEY on the immune cells was evaluated under-stimulated and non-stimulated conditions to determine cellular death and cytokine production, post-exposure with 40, 400 or 4.000 μg mL-1 of WHEY or CAS. Flow cytometry was used to identify the monocyte and lymphocyte population. Cytokines were measured from the supernatants of 24 hour-old PBMC cultures. Results: Compared to CAS, WHEY significantly decreased lymphocyte death at 4.000 μg mL-1 in both groups of individuals with no effects on the monocyte population regardless of the group. At the same concentration (4.000 μg mL-1), WHEY increased TNF and IL-10 cytokine levels in the stimulated PBMC supernatant from CLD patients. Conclusion: Compared to CAS, WHEY exerted immunomodulating effects in CLD patients. A similar response may be anticipated for other pathological conditions in which high stress and immune dysfunction are present.
Keywords: immunomodulation